Hospice palliative care professionals' opinions, emotions, skills and ethical reflections during the first phase of the COVID-19 pandemic. (2nd January 2022) - Bovero, Andrea; Tosi, Chiara
Abstract : Background: The COVID-19 pandemic presented an extraordinary challenge for palliative care in Italy. Aim: To investigate the opinions, emotions, skills, resources, critical issues and ethical aspects of palliative care encountered by hospice palliative care professionals in Italy. Methods: Content analysis was performed on the answers to a survey distributed by e-mail. Findings: A sample of 42 professionals completed the survey. They commonly experienced the pandemic as a challenging situation that highlighted the need for an upgrade to the Servizio Sanitario Nazionale (SSN). Conflicting emotions emerged, namely fear, frustration and sadness, but also hope and solidarity. The lack of adequate personal protective equipment and the fact that caregivers were unable to access their patients due to concerns of infection were the most critical problems. The need for greater training on communication skills and training on end-of-life issues were emphasised by the participants of the survey. Regarding ethical aspects of providing palliative care during the COVID-19 pandemic, the importance of guaranteeing humane care and patients' dignity was mentioned. Conclusion: The importance of specific training regarding end-of-life care and the central role of empathic communication were confirmed.